Chasing the Beginning of Reionization in the JWST Era - Christopher Cain; Garett Lopez; Anson D’Aloisio; Julian B. Muñoz; Rolf A. Jansen; Rogier A. Windhorst; Nakul Gangolli (The Astrophysical Journal)
Recent JWST observations at z  > 6 may imply galactic ionizing photon production above prior expectations. Under observationally motivated assumptions about escape fractions, these suggest a z  ~ 8–9 end to reionization, in tension with the z  < 6 end required by the Ly α forest. In this work, we use radiative transfer simulations to understand what different observations tell us about when reionization ended and when it started. We consider a model that ends too early ( z _end  ≈ 8) alongside two more realistic scenarios with z _end  ≈ 5: one starting late ( z  ~ 9) and another early ( z  ~ 13). We find that the latter requires up to an order-of-magnitude evolution in galaxy ionizing properties at 6 <  z  < 12, perhaps in tension with measurements of ξ _ion by JWST, which indicate little evolution. We study how these models compare to recent measurements of the Ly α forest opacity, mean free path, intergalactic medium thermal history, visibility of z  > 8 Ly α emitters, and the patchy kSZ signal from the cosmic microwave background (CMB). We find that neither of the late-ending scenarios is strongly disfavored by any single data set. However, a majority of observables, spanning several distinct types of observations, prefer a late start. Not all probes agree with this conclusion, hinting at a possible lack of concordance arising from deficiencies in observations and/or theoretical modeling. Observations by multiple experiments (including JWST, Roman, and CMB-S4) in the coming years will establish a concordance picture of reionization's beginning or uncover such deficiencies.